Taking institutions seriously rethinking the political economy of development in the Philippines - Nye, John V. C. (Asian Development Review)
Despite the current fashion for issues such as institutional transparency or corruption, the modern policy development literature does too little to integrate the core ideas of modern political economy with standard economic theory. Little is done to distinguish the advice given to developing countries especially on macroeconomic aggregates from that given to richer nations with stronger instituti onal environments. The essay uses the Philippines as a case study to suggest what is wrong with leading prescriptions. It suggests a framework that starts from a basic analysis of sectoral distortions to identify the areas where ideal reforms are likely to have the most impact and then pairs such analysis with more institutionally consistent considerations to see which second best reforms are most likely to be implemented. The focus should be on incentive compatible, self-enforcing policy mechanisms which usually imply greater market access and decentralized competition.